Aged and Aging - Wasilah Rochmah Wasilah Rochmah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Since the last two decades the history has witnessed that aging and gerontology have been the focus of extensive discourse and concern. Aging has arrived as an issue and object of study, and academic community recognized aging as a legitimate area of study. As the number of elderly has increased exponentially, the professional and paraprofessional occupations dealing with that problems of the elderly has also increased. Chronologically, a person is considered to be old if he/she experiences a long life. Old is not only viewed by its chronological aspect, but also by its physical and psychological aspects as well. Aging results in body structural and functional changes, and it generates impairment, disability, and sometimes conform to a disease. The mechanisms and factors underlying aging process are still controversial. In attempts to explain aging process some numbers of theories have been proposed. It is, therefore, the emerging issues concerning old and aging process are: how the aging process takes place and which theories are still plausible? Aging process is a life-long process, characterized by body- failures in maintaining homeostatic conditions to physiological stresses. There are a variety of theories of aging that are proposed in which some of them are still plausible.Keywords: elderly - aging process - body structural & functional changes - impairment & disability -theories of aging